Reading in the “Grafted Space”: Public/Private Pleasure Reading and Sexual Identity - Pecoskie, Jen (Mémoires du livre / Studies in Book Culture, 2012)
From research on pleasure reading, it is understood that reading “not to feel alone” is a role of reading for those who need to reconcile differentness or avoid stigmatization. This paper aims to explain the dynamic between social and solitary reading for female, adult readers who self-identify as lesbian, gay, bisexual, or queer. This qualitative work uses in-depth, open-ended interviewing and analysis follows the principles of naturalistic inquiry including emergent, inductive methods. The interconnectedness of participants’ solitary and social reading as related to identity is explored through the ways in which the readers connect their private reading to various levels of their public selves. This work presents an original contribution to reading research—the grafted space of reading, where the social and the solitary are inseparable. Reading in the grafted space is as much about the personal identities of the reader as it is about connecting with others and reinforcing social relations.